Method for Determining Antiheparin Activity of Platelets and Erythrocytes - Poplawski, A; Niewiarowski, S (Thrombosis and Haemostasis, 1965)
A method for determining antiheparin activity of platelets and erythrocytes is described. The neutralization of various concentrations of heparin by various amounts of protamine sulphate or tested material is measured simultaneously. Results are expressed in mean equivalent of protamine sulphate (PS) standard solution. The normal values of antiheparin activity of platelets and erythrocytes in human and in various animals are given.